Relationship Between Knowledge Base and Innovation-Driven Growth: Moderated by Organizational Character - Yu, Dengke; Yan, Hongling (Frontiers in Psychology, 2021)
Purpose - In the background of innovation-driven growth strategy of Chinese government, this study aims to explore the impact of knowledge base on firm innovation-driven growth, which is moderated by organizational character. Design/methodology/approach - Based on the data of 965 Chinese listed companies, some hypotheses were tested by the method of hierarchical regression analysis. Findings - Organizational growth relies on both technological innovation and business model innovation, as well as their interactive effect. Knowledge base, both breadth and depth, makes positive impact on enterprise’s innovation-driven growth. In the impacting mechanism, explicit organizational character not only makes direct positive effects on business model innovation but also strengthens the effect of knowledge breadth on business model innovation. On the contrary, implicit organizational character is not significantly related to innovation. Research limitations/implications – In order to achieve growth, enterprises are suggested to adopt such a dual innovation strategy - led by technological innovation and supplemented with business model innovation, which is supported by the integrated management of intangible resources - deep and bread knowledge and explicit organizational character. Originality/value - A new theoretical framework of organizational innovation-driven growth was proposed. The realization paths of innovation-driven growth were explored. The idea of collaborative governance of knowledge base and organizational character was raised.